Engineering properties of factory manufactured paving blocks utilizing steel slag as cement replacement. (December 2021) - Hussain, Iqrar; Ali, Babar; Rashid, Muhammad Usman; Amir, Muhammad Talha; Riaz, Sobia; Ali, Asif
Abstract: Vibropressing compaction of dry mixed concrete has increased the production rate of paving blocks, as it eradicated the need of formwork to hold the fresh concrete mixture in shape after molding. This technique also optimized the cost-benefit ratio as it helps in achieving high strength blocks with the minimum utilization of water and cement. In this study, effect of steel slag powder (SSP) was studied as the cement replacement material on the physical and mechanical properties of paving blocks. The cement was replaced with SSP as 5%, 10%, 15%, 20%, 25% and 30% by mass. Incorporation of SSP improved the finishing of paving blocks. The results of compression testing revealed that paving blocks incorporating 5–15% SSP as the cement replacement showed higher strength than the control paving block. This improvement is entirely credited to the better packing of constituent particles caused by the filling effect of SSP. The increase in ultrasonic pulse speed also confirmed that 5–15% SSP improved the density of paving blocks. However, the impact toughness of paving blocks reduced with the rise in SSP percentage beyond 5%.